PSMD2 promotes the progression of bladder cancer and is correlated with immune infiltration - Wang, Song; Wang, He; Zhu, Shaoxing; Wang, Zongping (Frontiers in Oncology, 2022)
PSMD2 plays an oncogenic role in multiple human malignancies, while it is still unclear that the potential roles and underlying mechanisms of PSMD2 in BCa. The RNA-seq from TCGA and GTEx database was utilized to preliminarily analyze the expression of PSMD2 in BCa tissues, qRT-PCR was adopted to verify the PSMD2 expression in BCa cell lines. Cox regression analyses were applied to assess the prognostic values of PSMD2 in BCa. GSEA analysis was used to explore the underlying mechanisms of PSMD2. In vitro assays such as wound healing and colony formation assays were applied to determine the carcinogenesis of PSMD2 in BCa. xCell and ssGSEA algorithms were applied to analyze the associations of PSMD2 with TIME. The results revealed that in comparation with normal bladder tissues and cell line, PSMD2 was found significantly elevated in BCa tissues and cell lines. Elevated expression of PSMD2 can independently predict unfavorable OS for BCa patients. The PSMD2 expression and other clinicopathologic factors were combined to develop a nomogram, which can help to predict OS for BCa patients. GSEA analyses revealed that the cell cycle, antigen processing and presentation, JAK-STAT signaling pathway, Toll like receptor signaling pathway, P53 and MAPK signaling pathway are remarkably concentrated in highly expressed PSMD2 BCa tissues. Knockdown of PSMD2 could remarkably inhibit the wound healing and colony formation efficiency of BCa cells. xCell analysis revealed that overexpressed PSMD2 is positively related to the Th2 cells infiltrates and expression levels of immune escape markers, and negatively associated with the infiltrating levels of NK T cell and CD8+ T cell. In conclusion, overexpressed PSMD2 is tightly linked to the immune infiltrates and promotes the progression of BCa.